2018
DOI: 10.4314/ahs.v18i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic detection of antibiotic resistance of Pseudomonas aeruginosa isolated from urinary tract infections

Abstract: BakgroundPseudomonas aeruginosa is a major nosocomial uropathogen. It can tolerate a wide variety of physical conditions and many antibiotics by different resistance mechanisms.ObjectivesThis study aimed to investigate the mechanisms of antibiotics resistance in uropathogenic P. aeruginosa clinical isolates.MethodsTwo hundred sixty six urine samples were collected from Zagazig University Hospitals, Zagazig, Egypt. P. aeruginosa isolates were identified using standard microbiological tests. The sensitivity to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 31 publications
5
25
5
Order By: Relevance
“…The MBL genotype, bla IMP was only detected in 1 sample (1.25%) while bla VIM was not detected in any of the sample. Similar findings were reported in Egypt by Abbas et al, [56], where no VIM genes was detected by PCR analysis. In contrast, Zafer et al, and Adjei et al, [49,55] reported a prevalence of 58.2%…”
Section: Discussionsupporting
confidence: 91%
“…The MBL genotype, bla IMP was only detected in 1 sample (1.25%) while bla VIM was not detected in any of the sample. Similar findings were reported in Egypt by Abbas et al, [56], where no VIM genes was detected by PCR analysis. In contrast, Zafer et al, and Adjei et al, [49,55] reported a prevalence of 58.2%…”
Section: Discussionsupporting
confidence: 91%
“…The MBL genotype, bla IMP was only detected in 1 sample (1.25%) while bla VIM was not detected in any of the sample. Similar findings were reported in Egypt by Abbas et al, [56], where no VIM genes was detected by PCR analysis. In contrast, Zafer et al, and Adjei et al, [49,55] reported a prevalence of 58.2% and 29% respectively in VIM-2.…”
Section: Discussionsupporting
confidence: 91%
“…An increasing trend was also observed for bla PER and bla GES ESBL traits. On the other hand, bla VIM and bla IMP were the most prevalent metallo-β-lactamases resistance encoding genes which showed a remarkable increase, along with bla NDM [ 84 , 88 , 90 , 91 , 92 , 93 ].…”
Section: Resultsmentioning
confidence: 99%